THE TEMPLE IN 2 MACCABEES – DYNAMICS AND EPISODES - Jordaan, Pierre J (Journal for Semitics, 2017)
Scholars differ among each other about the importance of the Jerusalem temple in 2 Maccabees. Some see the temple as of minor importance while others are of the opinion that the temple takes centre stage in this book. This article concurs with the second view. However, it goes further by also exploring crucial temple dynamics. These temple dynamics are determined by certain pre-set criteria and centre mainly on the relationship between God and the nation. The result is that three different temple episodes can be distinguished. The positive/negative view of each temple episode is determined by this relationship between the nation and God. This opens a new way of exploring 2 Maccabees.